Pengembangan Aplikasi Manajemen Apotek Berbasis Aplikasi Visual Studio 2022 - Prawisty, Amanda Velira; Ayuningtyas, Pinasthi; Basatha, Rizky (Lembaga Yasin AlSys, 2025)
The development of information technology has encouraged digitalization in various sectors, including the pharmaceutical industry. This research aims to develop a Visual Studio 2022-based pharmacy management application that can increase the efficiency and accuracy of pharmacy data management, including drug data, sales transactions and stock. The research methodology uses a software engineering approach which includes requirements analysis, design, implementation, testing and maintenance stages. This application is designed with an intuitive and responsive user interface using the C++ programming language and a SQL Server database for data management. Application test results show optimal performance in supporting pharmacy business processes, such as stock management, transaction recording and automatic reporting. The conclusion of this research is that the application developed is able to provide an effective and efficient solution to overcome challenges in managing traditional pharmacies. Further development is needed to integrate the application with electronic payment systems and telemedicine features to improve overall pharmacy services.